Health Education in Elementary Schools: Introducing Balanced Nutrition to Elementary School Children - Nurfadhillah, Wardah (Jurnal Pendidikan, Kesehatan dan Olahraga, 2024)
This article discusses the importance of health education in elementary schools, with a particular focus on introducing balanced nutrition to children. Balanced nutrition serves as the foundation for a healthy diet, which can help prevent various health issues in the future. Through creative and participatory learning approaches, including parental involvement and the use of interactive methods, children can better understand the concept of nutrition and apply it in their daily lives. Furthermore, this article identifies challenges in implementing nutrition education, such as varying levels of understanding across different regions, cultural influences, and the lack of training for educators. By addressing these challenges and strengthening collaboration among schools, parents, and communities, it is hoped that a healthier generation emerges, aware of the importance of balanced nutrition